Oral Swab Specimens Tested With Xpert MTB/RIF Ultra Assay for Diagnosis of Pulmonary Tuberculosis in Children: A Diagnostic Accuracy Study. (17th May 2022) - Cox, Helen; Workman, Lesley; Bateman, Lindy; Franckling-Smith, Zoe; Prins, Margaretha; Luiz, Juaneta; Van Heerden, Judi; Ah Tow Edries, Lemese; Africa, Samantha; Allen, Veronica; Baard, Cynthia; Zemanay, Widaad; et al.
Abstract: Background: Microbiologic diagnosis of childhood tuberculosis may be difficult. Oral swab specimens are a potential noninvasive alternative to sputum specimens for diagnosis. Methods: This was a prospective diagnostic accuracy study of oral swab specimens (buccal and tongue) for pulmonary tuberculosis diagnosis in children (aged ≤ 15 years) in 2 South African hospital sites. Children with cough of any duration as well as a positive tuberculin skin test result, tuberculosis contact, loss of weight, or chest radiograph suggestive of pulmonary tuberculosis were enrolled. Two induced sputum specimens were tested with Xpert MTB/RIF (or Xpert MTB/RIF Ultra) assay and liquid culture. Oral swab specimens were obtained before sputum specimens, frozen, and later tested with Xpert MTB/RIF Ultra. Children were classified as microbiologically confirmed tuberculosis, unconfirmed tuberculosis (receipt of tuberculosis treatment), or unlikely tuberculosis according to National Institutes of Health consensus definitions based on sputum microbiologic results. Results: Among 291 participants (median age [interquartile range], 32 [14–73] months), 57 (20%) had human immunodeficiency virus (HIV), and 87 (30%) were malnourished; 90 (31%) had confirmed pulmonary tuberculosis (rifampicin resistant in 6 [7%] ), 157 (54%), unconfirmed pulmonary tuberculosis, and 44 (15%), unlikely tuberculosis. A single oral swab specimen was obtained from 126 (43%) of the participants (tongue in 96 and buccal in 30) and 2 swab specimens from 165 (57%) (tongue in 110 and buccal in 55). Sensitivity was low (22% [95% confidence interval, 15%–32%]) for all swab specimens combined (with confirmed pulmonary tuberculosis as reference), but specificity was high (100% [91%–100%]). The highest sensitivity was 33% (95% confidence interval, 15%–58%) among participants with HIV. The overall yield was 6.9% with 1 oral swab specimen and 7.2% with 2. Conclusions: Use of the Xpert MTB/RIF Ultra assay with oral swab specimens provides poor yield for microbiologic pulmonary tuberculosis confirmation in children. Abstract : Oral swab specimens provide a potential alternative to sputum specimens for diagnosing childhood pulmonary tuberculosis. However, in a prospective diagnostic accuracy study, sensitivity for the Xpert MTB/RIF Ultra assay was poor, 22% overall. Specificity was high, and a second specimen did not increase yield.